THE USE OF UNDERCOVER GAME TO ENHANCE STUDENTS’ VOCABULARY ACHIEVEMENT - Muhammad Anwar Rosyidi; Fahriany Fahriany; Desi Nahartini (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
This study aimed to find empirical evidence of the use of undercover games on students’ vocabulary achievement. The study used a quantitative method with a quasi-experimental design and purposive sampling technique. The total sample of this study was 70 students divided into two classes: experimental and controlled classes. The population of this study was the eighth-grade students of SMPN 108 Jakarta. The data was gained through pre-test and post-test. Both data from the tests were analyzed using a t-test in SPSS 25. The mean score in the post-test showed significant improvement between the pre-test and post-test. In the pre-test, the experimental class gained 65.82, while the controlled class gained 70.23. In post-test, the experimental class gained 78.20, and the controlled class gained 77.08. The test of the hypothesis showed that sig. 2 tailed was 0.076 while the determined alpha ? was 0.05, which meant that 0.076>0.05. It is supported by the result of effect size, which was 1.02 as well. It can be said that the Ho (Null Hypothesis) was rejected, and the Ha (Alternative Hypothesis) was accepted. Therefore, the undercover game strongly affected students’ vocabulary achievement.